(6 - 5x)(6 + 5x)=?

(6-5x)(6+5x)=

you need to visualize the foil method, Krill.

first start with the 6 in the first set and multiple with the second set <whole>

6 (6+5x) = 36+30x

second start with the -5x in the first set and multiple with the second set <whole>

-5x (6+5x) = -30x-25x^2

note

x^2 = x to the 2nd power

after the basic foil is done, you must combine all like terms.

x^2 terms may not be combine with 2x terms in short.

36-25x^2 should be your answer.

## Comments

Fred, do you know the difference between equation and expression?